Pengaruh Internet Banking Terhadap Kinerja Perbankan - Muhammad Arif; Erni Masdupi (Jurnal Ecogen, 2020)
Internet banking is an interesting topic. It has become one of the most important and modern applications that have many benefits. This research objects to analyze the impact of internet banking on banking performance at banks listed on the Indonesia Stock Exchange (IDX). This research also examines banking ratios such as size, capital, credit risk, expense management, liquidity, and macroeconomic factors, such as inflation and economic growth. The population that used in this research were all financial sector companies in the banking subsector listed on IDX. While the sample in the research was determined by purposive sampling method, so that 58 samples of companies were obtained during the 2010-2019 period. The data type is secondary data obtained by the IDX and the sample companies' annual reports. The data were analysed using multiple linear regression by way of SPSS 25. The results of the research concluded that internet banking has a negative and insignificant effect on banking performance, size and capital have a positive and significant effect. Credit risk, expense management and economic growth have a negative and significant effect on banking performance. Meanwhile, liquidity and inflation have a negative and insignificant effect on banking performance. Keywords : banking performance, internet banking, banking ratios